RIFM fragrance ingredient safety assessment, propyl propionate, CAS Registry Number 106-36-5. (15th December 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: Summary: The existing information supports the use of this material as described in this safety assessment. Propyl propionate was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data show that propyl propionate is not genotoxic. Data on propyl propionate provide a calculated margin of exposure (MOE) >100 for the repeated dose toxicity, reproductive toxicity, and local respiratory toxicity endpoints. Data from read-across analog pentyl propionate (CAS # 624-54-4) show that there are no safety concerns for propyl propionate for skin sensitization under the current declared levels of use. The phototoxicity/photoallergenicity endpoints were evaluated based on ultraviolet (UV) spectra; propyl propionate is not expected to be phototoxic/photoallergenic. For the hazard assessment based on the screening data, propyl propionate is not persistent, bioaccumulative, and toxic (PBT) as per the International Fragrance Association (IFRA) Environmental Standards. For the risk assessment, propyl propionate was not able to be risk screened as there were no reported volumes of use for either North America or Europe in the 2015 IFRA Survey. Highlights: Propyl propionate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.